Identifikasi gejala, faktor risiko, dan pola paparan suhu rendah terhadap alergi dingin pada masyarakat tropis - Ledo, Naldi; Setyawan, Yuswanto (Holistik Jurnal Kesehatan, 2025)
Background: Cold allergy, or cold urticaria, is commonly reported in subtropical countries during extreme winter seasons. However, in tropical areas such as Indonesia, with increasing climate variability, there is a rising tendency of cold allergy symptoms in highland regions. The lack of adaptation to low temperatures in tropical populations may result in immunological hypersensitivity responses. Purpose: To identify symptoms, risk factors, and patterns of low temperature exposure to cold allergy in tropical communities. Method: This study used a cross-sectional design involving 200 respondents from Trawas, Prigen, and Pandaan. Cold exposure was assessed through questionnaires, categorized as high or low exposure. The dominant allergic symptoms, risk factors, and cold exposure patterns were identified. Chi-Square analysis tested the association between location and cold exposure, while Spearman correlation examined the relationship between exposure level and number of symptoms. Results: Chi-Square test showed a significant association between location and cold exposure (p = 0.0125), while Spearman correlation showed a moderate positive correlation between cold exposure and number of symptoms (ρ = 0.421; p = 0.0031). Trawas showed the highest rate of cold exposure with dominant symptoms being urticaria and itching, while Prigen showed prolonged exposure and symptoms like rash due to high humidity. Conclusion: There is a significant association between location and level of cold exposure, and a moderate positive correlation between cold exposure and number of allergic symptoms. Cold allergy is present even in tropical climates, especially in highland areas, indicating the need for clinical attention and climate-adaptive public health strategies. Suggestion: Further research should be conducted by adding more specific environmental variables such as air humidity, actual temperature in objective units, and the level of chronic exposure to low temperatures.   Keywords: Cold Allergy; Exposure to Low Temperatures; Symptoms; Tropical Communities.   Pendahuluan: Alergi dingin atau urtikaria dingin umumnya terjadi di negara subtropis saat musim dingin ekstrem. Namun, di wilayah tropis seperti Indonesia, khususnya daerah dataran tinggi, fluktuasi suhu akibat perubahan iklim mulai memicu peningkatan kasus alergi dingin. Kurangnya adaptasi tubuh terhadap suhu rendah dapat menimbulkan reaksi imun berupa hipersensitivitas. Tujuan: Untuk mengidentifikasi gejala, faktor risiko, dan pola paparan suhu rendah terhadap alergi dingin pada masyarakat tropis. Metode: Penelitian ini menggunakan pendekatan kuantitatif dengan desain cross-sectional, melibatkan 200 responden dari Trawas, Prigen, dan Pandaan. Data dikumpulkan melalui kuesioner yang mencakup tingkat paparan suhu, jumlah gejala alergi, dan lokasi tempat tinggal. Uji Chi-Square digunakan untuk menguji hubungan antar variabel kategori, sedangkan uji Spearman digunakan untuk melihat korelasi antara paparan dan gejala. Hasil: Uji Chi-Square menunjukkan hubungan signifikan antara lokasi dan paparan suhu dingin (p = 0.0125). Uji Spearman menunjukkan korelasi positif sedang antara tingkat paparan suhu dan jumlah gejala alergi (ρ = 0.421; p = 0.0031). Trawas memiliki tingkat paparan tertinggi dengan gejala dominan berupa gatal dan biduran, sedangkan Prigen menunjukkan paparan dingin berkepanjangan dengan gejala berupa ruam karena kelembaban tinggi.Simpulan: Terdapat hubungan signifikan antara lokasi dan tingkat paparan suhu dingin, serta korelasi positif sedang antara paparan dan gejala alergi. Fenomena alergi dingin dapat terjadi pada masyarakat tropis, terutama di dataran tinggi, sehingga diperlukan perhatian klinis dan strategi kesehatan berbasis adaptasi iklim. Saran: Penelitian lanjutan sebaiknya dilakukan dengan menambahkan variabel lingkungan yang lebih spesifik seperti kelembaban udara, suhu aktual dalam satuan objektif, serta tingkat paparan kronis terhadap suhu rendah.   Kata Kunci: Alergi Dingin; Gejala; Masyarakat Tropis; Paparan Suhu Rendah.